A peça de arte móvel da Freixiosa (Miranda do Douro-Portugal). Primeiros avanços na sua contextualização e interpretação - Sanches, Maria de Jesus; Teixeira, Joana Castro (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2020)
The present text aims to make known a schist artefact engraved with abstract motifs according to a palaeolithic style. The artefact, deposited in the Natural History and Science Museum of the University of Porto (MHNC-UP), is from Freixiosa in Miranda do Douro county. Our aim is to describe and contextualize it in the scope of the regional rock and portable art dated from the ends of the Upper Palaeolithic to the Epipalaeolithic and also to establish possible connections to other Iberian areas as, for example, the Cantabria